2019
DOI: 10.3390/ijerph16030502
|View full text |Cite
|
Sign up to set email alerts
|

Social Norms Influencing the Local Food Environment as Perceived by Residents and Food Traders: The Heart Healthy Hoods Project

Abstract: Exploring subjective elements of the food environment remains key to understand why and how residents purchase food. Our aim was to explore and describe the social norms relating to the local food environment and food purchasing behaviors, as perceived by residents and food traders in Madrid, Spain. This qualitative study took place in a middle socioeconomic status neighborhood of Madrid between January 2015 and May 2016. We conducted 35 semi-structured interviews. We used stratified purposive sampling to recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Much insight can be gained into the context in which everyday food decisions are made by adopting alternative methodologies, as illustrated in three of the studies in this special issue. For instance, Sandín Vázquez and colleagues [9] adopted a qualitative approach and interviewed residents, neighborhood workers, and food traders to better capture social aspects related to food purchasing behaviors in a neighborhood of Madrid. Main key drivers of purchasing decisions emerging from the study were the importance of tradition and the trust and social relationships between customers and the food traders, the time scarcity associated with modern life, which drove younger residents towards supermarkets with greater ranges and convenience of food and longer opening hours, as well as the reduced purchasing power of individuals, which had a direct impact on purchasing decisions.…”
Section: Alternative Methods To Gain Insights Into Food-related Dementioning
confidence: 99%
“…Much insight can be gained into the context in which everyday food decisions are made by adopting alternative methodologies, as illustrated in three of the studies in this special issue. For instance, Sandín Vázquez and colleagues [9] adopted a qualitative approach and interviewed residents, neighborhood workers, and food traders to better capture social aspects related to food purchasing behaviors in a neighborhood of Madrid. Main key drivers of purchasing decisions emerging from the study were the importance of tradition and the trust and social relationships between customers and the food traders, the time scarcity associated with modern life, which drove younger residents towards supermarkets with greater ranges and convenience of food and longer opening hours, as well as the reduced purchasing power of individuals, which had a direct impact on purchasing decisions.…”
Section: Alternative Methods To Gain Insights Into Food-related Dementioning
confidence: 99%
“…Sustainable agro-food consumption is related to diverse macro-and individual-level factors. For instance, macro factors such as the availability of green foods [3,[12][13][14], the affordability of certain food options [5,9,10,[15][16][17], the health and safety concerns of organic agro-foods [4,7,10,[18][19][20][21], transportation and distributions systems [22][23][24][25], and the ecological concerns of the food supply [7,12,26,27] were inspected from previous studies. In recent years, more individual factors were examined, for example, consumers' awareness on SAF purchasing [12,[28][29][30], perceived values of green food [31], and the shifting social norms over years of promulgation on SAF consumption [10,17,19,20,32].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…In particular, social norms, referring to beliefs, values, attitudes, and behaviors of a group of people, play an essential role in sustainable purchasing behavior from end users' view [20]. Exploring social norms of SAF consumption remains key to understanding consumers' perspectives and purchase intention [10,19]. Studies on the effectiveness of social norms have shown that social message exposure may influence consuming choices in food intakes [20].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations